Saint Thomas Aquinas and Imam Al-Ghazali on the Attainment of Happiness - Shah, Rania (The international journal of religion and spirituality in society, 2015)
In early philosophically oriented societies, happiness was a prominent theme in literature. This paper provides insight to the question of finding happiness or the ultimate goal in life based on the works of two prominent spiritual masters and theologians of the Islamic and Catholic faiths, Imam Al-Ghazali (1058-1111) and Saint Thomas Aquinas (1225-1274). This paper explores the integration of theology and philosophy as a means to human flourishing, and makes the conclusion that this as much an issue of changing human nature and desires, as it is, a matter of faith.